The gross domestic product and its effect on spending on human resource development and community health in the Kingdom of Saudi Arabia - period. 2000 – 2017 - Halahleh, Mamoun Khalaf; Mohammed, Elsiddig Yousif (Journal of Economic, Administrative and Legal Sciences, 2021)
The objective of this study is to analyze the gross domestic product (GDP) and its impact on the expenses on the development of human resources and the community health in the kingdom of Saudi Arabia period 2000/2017. In fact, the GDP has been used as a separate variable while the expenditure on both the human resource development and community health in Saudi Arabia is used as a follow-up variable. an analytical prescriptive approach has been followed concluding that there is a strong moral effect of spending on human resource development as a percentage of GDP amounted to 1.03. In fact, through a descriptive analytical approach, this study concluded that there is a relationship with a strong moral impact of spending on both human resource development, as a proportion of the gross domestic product, and health, as a percentage of GDP amounted to 1.09.. The study also recommended the increase of the general public spending on human resources, as a percentage of local production and the increase of the proportion of public spending allocated to community health and localization of treatment within the Kingdom of Saudi Arabia.